Detection and Prediction of Internal-Caused Fire in Tunnel Cable by an Equivalent Transient Thermal Circuit Model - Yanwen Wang; Xuran Zhang; Le Wang; Yinsheng Wang (Advances in Civil Engineering)
Internal-caused cable fires are one of the most common cable fires, and anomalous temperature increase of the cable core is one of the first signs. However, when a cable is operating with electricity, the temperature of the core conductor cannot be monitored directly; therefore, this characteristic cannot be used in detection and prediction of internal-caused fire in electric cable effectively. An analogous transient thermal circuit model is created, simplified, and optimized to properly compute the temperature of the cable core. Afterward, by using the cable internal-caused fire experimental platform and adjusting current carrying capacity of the tested cable, an experiment is conducted for stimulating the very early stage of three-core cable internal-caused fire. The maximum relative errors of the transient thermal circuit model and the trisection transient thermal circuit model are less than 10% when comparing the experimental data with the calculation results, and the average relative error of the calculated value of trisection transient thermal circuit model is 1.08% after layered optimization. The algorithm model can satisfy the requirement for early detection and prediction in the very early stage of cable internal-caused fire.